2008
DOI: 10.4161/cc.7.22.7101
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-mediated differentiation of neural/neuronal cells from epithelial ovarian precursors in vitro

Abstract: We reported earlier that occasional neurons evolve in human cultures of pluripotent ovarian epithelial stem cells. In subsequent experiments, frequent transdifferentiation into neural stem cells (NSC) and differentiating neurons was observed in human ovarian epithelial stem cells and porcine granulosa cells after exposure to certain combinations of sex steroids. Testosterone (TS), progesterone (PG) or estradiol (E2) alone do not increase the emergence of neurons. However, a mixture of TS + PG after E2 pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 24 publications
(27 reference statements)
0
42
0
Order By: Relevance
“…As a continuation of our recent study dealing with ovarian epithelial cells 2 we tested the effect of Neurobasal/B27 neuron culture medium used for growth and long-term viability of hippocampal neurons (B27 medium) 8 on cultured OSE cells. Among other components, this medium contains undisclosed concentrations of progesterone and retinol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a continuation of our recent study dealing with ovarian epithelial cells 2 we tested the effect of Neurobasal/B27 neuron culture medium used for growth and long-term viability of hippocampal neurons (B27 medium) 8 on cultured OSE cells. Among other components, this medium contains undisclosed concentrations of progesterone and retinol.…”
Section: Resultsmentioning
confidence: 99%
“…1 Regarding transdifferentiation into neurons, umbilical cord blood, amniotic epithelial cells, bone marrow stem cells, and mobilized peripheral blood CD133 + cells can be transdifferentiated into neural stem cells (NSC) by fibroblast growth factor-1, 12-Otetradecanoylphorbol-13-acetate (protein kinase C activator), isobutylmethylxanthine (a Sex steroid-mediated reprogramming of vascular smooth muscle cells to stem cells and neurons non-specific inhibitor of phosphodiesterases), and forskolin (protein kinase A activator), or all-trans-retinoic acid and 2-merkaptoethanol (reviewed in ref. 2). These substances are not suitable for treatment in vivo, however.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bukovsky et al [9] observed that when porcine ovarian granulosa cells were cultured in vitro, they changed their morphology into fibroepithelial phenotype. Moreover, after exposure of cells to the mixture of testosterone and progesterone after pretreatment with estradiol, a majority of granulosa cells transdifferentiated into neuron-like cells.…”
Section: Granulosa Cells and Ability For Transdifferentiationmentioning
confidence: 99%
“…Within 10 min (panel B), however, the optically dense organelles are apparent in the extended arm (solid black arrow) within adjacent oocyte cytoplasm (red arrowhead) and distant oocyte regions (red arrow). In reality, normal granulosa cells exhibit fibroblastlike morphology in culture (Bukovsky et al, 2008b), and in vivo the granulosa cells originate from the same precursors as germ cell, that is, the OSC (Bukovsky et al, 1995(Bukovsky et al, , 2004.…”
Section: Development Of Oocytes and Parthenogenetic Embryos In Vitromentioning
confidence: 99%